2014
DOI: 10.1590/1809-4503201400030015
|View full text |Cite
|
Sign up to set email alerts
|

The performance of various anthropometric assessment methods for predicting low birth weight in adolescent pregnant women

Abstract: ABSTRACT:Objective: To evaluate the performance of various anthropometric evaluation methods for adolescent pregnant women in the prediction of birth weight. Methods: It is a cross-sectional study including 826 adolescent pregnant women. In the pre-pregnancy body mass index (BMI) classification, the recommendations of the World Health Organization were compared with that of the Brazilian Ministry of Health and the Institute of Medicine (IOM) of 1992 and 2006. The gestational weight gain adequacy was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
10

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 21 publications
1
2
0
10
Order By: Relevance
“…Se identificaron 2601 referencias. La revisión sistemática incluyó cinco estudios que cumplieron los criterios de selección previamente establecidos (11)(12)(13)(14)(15) (Figura 1).…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Se identificaron 2601 referencias. La revisión sistemática incluyó cinco estudios que cumplieron los criterios de selección previamente establecidos (11)(12)(13)(14)(15) (Figura 1).…”
Section: Resultsunclassified
“…Los estudios se desarrollaron en establecimientos de salud públicos de los Estados Unidos (12) , Brasil (13,14) , Italia (11) y China (15) . Cuatro estudios utilizaron un diseño de cohorte retrospectiva (12,15) y uno de cohorte prospectiva (11) .…”
Section: Características De Los Estudios Incluidosunclassified
See 2 more Smart Citations
“…l [ 8 ], who described the discordance between CDC and IOM criteria to classify pre-pregnancy BMI in pregnant adolescents; and the study performed by Barrios et al . [ 23 ], in a group of Brazilian pregnant adolescents, Barrios et al . assessed pre-pregnancy BMI using WHO, IOM and the Ministry of Health of Brazil criteria and concluded that criteria from the Ministry of Health of Brazil should be used to assess pregnant adolescents.…”
Section: Discussionmentioning
confidence: 99%